Tinjauan Umum Aliran Khawarij, Murji’ah, Jabariyah dan Qadariyah - Sabirin, Muh. Syahril; Jafar, Usman; Abbas, Nurlaelah (CV. ITTC INDONESIA, 2026)
The death of the Prophet Muhammad (peace be upon him) gave rise to political and theological dynamics within the Muslim community. The conflicts during the period of the Rightly Guided Caliphs, particularly following the arbitration (tahkim) between Ali ibn Abi Talib and Muawiyah ibn Abi Sufyan, resulted not only in political fragmentation but also in the emergence of various theological schools in Islam. This study aims to examine the historical background and main doctrines of the Khawarij, Murji’ah, Jabariyah, and Qadariyah, especially concerning issues of faith, major sins, and divine decree (qada and qadar). This research employs a qualitative-descriptive method with a library research approach by analyzing relevant books, journals, and scholarly articles. The findings indicate that the Khawarij and Murji’ah emerged as responses to political conflict, while the Jabariyah and Qadariyah developed due to differing interpretations of human will and freedom within God’s decree.